Evaluation of the Diameter, Heat Resistance, and Absorbability of Sheep Wool Originated from Selected Polish Breeds - Anna Wyrostek; Katarzyna Czyż; Kamila Hapka (Journal of Natural Fibers)
Sheep’s wool is a renewable, constantly growing resource, so it needs to be developed. Originally, it was mostly used in the textile industry, but the replacement by other materials resulted for some breeds in the deterioration of its quality and the need to look for alternative uses. Today, thanks to its properties, in addition to its traditional uses in a wide range of textiles, sheep’s wool is also used as an insulating material, fertilizer, or sorbent. In this research, wool originated from 3 Polish breeds of sheep, Olkuska, Pomeranian, and Polish Pogórza sheep was evaluated. Diameter, coefficient of variation, comfort and prickle factors, % of medullated fibers, heat resistance, and absorption were evaluated. It was shown that the breeds differed in diameter and heat resistance. No differences were shown between the absorption properties of the wool. This research has shown that the wool characteristic with the greatest variation is its diameter. Understanding the properties of the wool of local breeds will allow it to be better managed, instead of treating it as waste.